Evaluasi Pemungutan Pajak Parkir Dalam Meningkatkan Penerimaan Pajak Daerah Di Kota Bekasi (Studi Pada Badan Pendapatan Daerah Kota Bekasi Tahun Anggaran 2019-2023) - Putri, Irma Nurmala; Wahyudin, Dian (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
Parking tax is one type of regional tax levied on parking business owners outside public roads, including car and motorcycle parking lots. This study aims to evaluate parking tax coltection in increasing regional tax revenue in Bekasi City. This study uses the policy evaluation theory of Alilliam Dunn with six evaluation consists of effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. This study also uses a descriptive qualitative method with data collection techniques in the form of data triangulation.The results of this study indicate that parking tax collection in Bekasi City for the Fiscal Years 2A19-2023 has not been well and optimally implemented in increasing regional tax revenue, specifically in the indicators of effectiveness, efficiency, adequacy, and accuracy. However, in the indicator of responsiveness, it has been well executed. The obstacles related to parking tax collection include: irregular periodic updating of the parking tax database (tax potential) in Bekasi City; unoptimized socialization of parking tax imposition according to applicable regulations; limitation on human resources of the Bekasi City Bapenda (Regional Revenue Agency); the absence of an integrated online system application among related regional organizations; certain parties who apparently control parking business areas; limited availability of parking tapping boxes; and unoptimized supervision, examination, and collection by the tax authorities on parking taxpayers. lmprovements that can be made include: improving the database of parking tax potential in Bekasi City; socializing parking tax imposition according to applicable regulations; enhancing the competence of the Bekasi City Bapenda human resources; developing an integrated online system application among related regional organization; conducting supervision and enforcement of Regional Regulations against certain parties who seem to control parking business areas; increasing the number of tapping boxes and other systems of information technology; optimizing supervision, examination, and collection efforts by the tax authorities on parking taxpayers